(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This modern method of making longitudinal structures of cast concrete suitable for Central Asian climatic conditions can be used to make thin monalite constructions of high density and strength. Preparation of cast-in-place concrete structures in such a rapidly changing climate is more difficult. When studying the problems of pouring concrete in dry hot climates, the researchers focused on the following issues: the influence of technological factors on other properties, including the development of methods of concreting